If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m(2) + 4(15.5) = m + 4(3) Reorder the terms for easier multiplication: 2m + 4(15.5) = m + 4(3) Multiply 4 * 15.5 2m + 62 = m + 4(3) Reorder the terms: 62 + 2m = m + 4(3) Multiply 4 * 3 62 + 2m = m + 12 Reorder the terms: 62 + 2m = 12 + m Solving 62 + 2m = 12 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 62 + 2m + -1m = 12 + m + -1m Combine like terms: 2m + -1m = 1m 62 + 1m = 12 + m + -1m Combine like terms: m + -1m = 0 62 + 1m = 12 + 0 62 + 1m = 12 Add '-62' to each side of the equation. 62 + -62 + 1m = 12 + -62 Combine like terms: 62 + -62 = 0 0 + 1m = 12 + -62 1m = 12 + -62 Combine like terms: 12 + -62 = -50 1m = -50 Divide each side by '1'. m = -50 Simplifying m = -50
| 5x-7=0 | | 0.5(x-12)=4 | | 5n+10=5 | | 29=a+5 | | 8(3x+1)=-80 | | -2=-(2-8) | | 2m+40=3m | | 4x+3.6+x=1.2 | | -6x-7=-3-8x | | 5v-3-4v=13 | | -6(5x+2)=198 | | -6(5x+2)=197 | | 5n+2n-(3-10n)= | | x-8=2x+3 | | 5(2+y)=7 | | 8(3x+1)=28 | | 48=8(x+2) | | 434=-31y | | m+5(m-1)=7 | | 15=-3(2q-1) | | 6x=-4.2 | | 2(8+p)=22 | | 3x-5y=0 | | -.98=m+1.0034 | | 7m-3m-6=6 | | 5-x-x=-1 | | y+y+2=18 | | 2(3t-8)-4t=10 | | 2x+5y=20 | | x+.5x=1726 | | x+1=2x | | 11x-1.3=1-2x |